Timely diagnosis and treatment of HELLP syndrome - Zapata Díaz, Betsy Micol (2020)
HELLP syndrome (HS) is a severe complication of pregnancy characterized by hemolysis, elevated liver enzymes and low platelets. It is one of the most serious maternal complications and is associated with high maternal and perinatal morbidity and mortality. Childbirth is the only effective treatment against HS. The most frequent complication of HS is hemorrhage, requiring blood transfusions and/or blood products to correct hypovolemia, anemia or coagulopathy; spontaneous liver hematoma is the most catastrophic problem. Perinatal mortality is directly related to gestational age. There is no consensus on HS management occurring before 34 weeks of gestation when maternal and fetal conditions are stable. The purpose of this review is to summarize the existing information about the timely management of HS. It is concluded that the birth route will depend on cervical conditions and maternal and fetal stability. Appropriate studies are needed to determine if there is benefit in expectant management in preterm pregnancies and in corticosteroids administration to improve platelet count in HS.